High impact minimum wages and heterogeneous regions - vom Berge, Philipp; Frings, Hanna; Paloyo, Alfredo R. (Bochum, 2013)
"We estimate the effects on wage and employment growth rates of the introduction and subsequent increases of a substantial minimum wage in the main construction industry of Germany. Using a regional dataset constructed from individual employment histories, we exploit the spatial dimension and border discontinuities of the regional data to account for spillovers between districts and unobserved heterogeneity at the local level. The results indicate that the minimum wage increased the wage growth rate for East Germany but did not have a significant impact on the West German equivalent. The estimated eff ect on the employment growth rate reveals a contraction in the East of about 2.6 to 3.1 percentage points for a one-standard-deviation increase in the minimum-wage bite, amounting to roughly half of the overall decline in the growth rate, but no significant change is observed for the West."